Educational Fee Setting Strategy Based on Parents’ Economic Capacity (A Study on the Implementation of the ZISWAF Method at SD Islam Sabilul Qur’an) - Yani Mulyani; Nina Napisah; Wina Sapitri; Badrudin; Qiqi Yuliati Zakiah (South Sulawesi Education Development (SSED), 2025)
This study examines the strategy of SD Islam Sabilul Qur’an Majalengka in setting educational fees according to parents’ economic capacity, the management and use of ZISWAF (Zakat, Infaq, Sedekah, and Wakaf) funds to support school financing, and the challenges and opportunities in implementing a ZISWAF-based funding model at a private Islamic elementary school. A qualitative case study approach was employed, involving in-depth interviews with school administrators, ZISWAF coordinators, teachers, and parents, as well as document review and field observations. Findings indicate that the school categorizes families into “very poor,” “poor,” “lower‐middle,” and “upper‐middle” groups based on income, assets, and dependents. Subsidies range from 50 % to 100 % of full tuition for qualifying families, while higher‐income families pay full fees and may contribute additional infak to bolster the school’s endowment. ZISWAF funds are collected from internal and external donors comprising regular zakat contributions, one‐time sedekah, and wakaf invested as a perpetual fund and are allocated to cover tuition gaps after a verification process involving document checks and home visits. This model has successfully reduced tuition arrears and ensured universal access regardless of socioeconomic status. However, challenges remain in defining clear income thresholds, expediting verification, and mitigating dependency on fluctuating donations. Opportunities include implementing a cloud‐based beneficiary management system, strengthening wakaf endowment management for sustainability, and enhancing parent engagement through regular forums. The study concludes that an integrated ZISWAF‐based financing mechanism can achieve equitable access and financial stability when combined with transparent procedures and community participation. Keywords: differential tuition, Islamic elementary school, educational financing, beneficiary verification, wakaf endowment;